Irrational performance beliefs and mental well-being upon returning to sport during the COVID-19 Pandemic: A test of dediation by intolerance of uncertainty - Wolfson, S.; Jooste, J.; Kruger, A. (Research Quarterly for Exercise and Sport, 2023)
Purpose This study examined the extent to which irrational performance beliefs and intolerance of uncertainty co-occur in relation to mental well-being among a sample of athletes and coaches (N = 94, M age = 31.99, SD = 12.81) upon their return to sport following COVID-19 disruptions.